ANALYSIS OF IMPACT OF MINERAL MATRIX OF RUNOVSHCHINSKA AREA RESERVOIR ROCKS ON THE ELASTIC AND ACOUSTIC PARAMETERS (BASED ON THE RESULTS OF MATHEMATICAL MODELLING) - Bezrodna, I.; Bezrodnyi, D.; Kozionova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Purpose of the work consists in the analysis of impact of rocks mineral matrix on the parameters of their elastic and acoustic anisotropy during the investigations of models of terrigenous reservoir rocks of Runovshchinska area. Methods of conditional moment functions using Mori-Tanaka computational pattern and least squares method were used to solve the problem. Authors developed 6 mathematical models of reservoir rocks of the region, based on the results of petrophysical studies carried out at the Institute of geology and authors` personal investigations. Based on the results of modeling for the model of pure quartz sandstone it was determined that main mineral of the matrix – quartz, – which determines almost all elastic and acoustic properties of the model, has dominant influence on the rock symmetry type. In case of changes in the aspect ratio, appearance of other minerals (mica, kaolinite, calcite, plagioclase, feldspar) and secondary elongated voids in the following models and with increase of the voids concentration, the typical symmetry type is mainly orthorhombic and transversely-isotropic. Acoustic symmetry of texture of the prevailing part of investigated models is planar transversely isotropic or axial orthorhombic. The last type of the acoustic symmetry is common for the sandstones that contain mica or kaolinite, fractured and cavernous sandstones. Planar symmetry type can indicate the presence of unidirectional compression stress. Axial symmetry type indicates the presence of unidirectional tensional stress. Complication of symmetry to the orthorhombic can be considered as the evidence of multiple compressions and tensions. Maximum values of differential coefficient of acoustic anisotropy (up to 10%) are close to the values of integral coefficient of acoustic anisotropy, but they vary in wider range. Specific directions where the value of this parameter are equal or close to zero can be found on the stereoprojections of indicating surface of differential coefficient of acoustic anisotropy. Elastic waves propagate accordingly to the laws for the isotropic medium along these directions. Besides mineral composition the shape of voids substantially influences the parameters of acoustic and elastic anisotropy. Fractures have definitely higher impact on the investigated parameters than caverns. Parameters of acoustic and elastic anisotropy are the indicators for the investigations of the same-type rocks with different parameters of mineral inclusions and void space structure. Developed models undoubtedly may be used during the interpretation of petrophysical and geophysical data to study the changes of the void space structure, types and concentration of rock-forming minerals in the rock.
Keywords: mathematical modelling; elastic anisotropy; sandstones of complex structure